Pin-by-Pin Coupled Transient Monte Carlo Analysis Using the iMC Code - Kim, HyeonTae; Kim, Yonghee (Frontiers in Energy Research, 2022)
In this article, we present a coupled multi-physics Monte Carlo reactor transient analysis framework implemented in the KAIST Monte Carlo iMC code. In the multi-physics framework, the time-dependent neutron transport calculation and the transient heat transfer analysis are done based on the predictor–corrector quasi-static Monte Carlo method and the three-dimensional finite element method, respectively. Using this high-fidelity analysis framework, we demonstrated the negative temperature feedback effect in two pressurized water reactor (PWR) transient scenarios. First, a 3-D burnable absorber-loaded fuel assembly was considered with all reflective boundary conditions. In this simple problem, a positive reactivity-induced transient was analyzed to characterize the reactor responses in view of the pin-wise power and temperature distribution. Second, the iMC multi-physics analysis is applied to a control rod withdrawal transient in the TMI-1 mini core problem, and detailed time-dependent results were provided and compared with the Serpent/SUBCHANFLOW analysis. In both cases, independent MC runs were performed to quantify the uncertainty of the multi-physics MC transient analysis.